ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN PT MUSTIKA RATU TBK. BERDASARKAN ANALISIS RASIO LIKUIDITAS, SOLVABILITAS, DAN RENTABILITAS - Asih Nurati; Burhanudin Burhanudin; Ratna Damayanti (JURNAL ILMIAH EDUNOMIKA, 2019)
This study is intended to determine the financial performance of PT Mustika Ratu Tbk. by analyzing financial data through financial ratios of liquidity, solvency and profitability. The data analyzed are company financial statements which include Balance Sheet, Profit / Loss, Cash Flow PT Mustika Ratu Tbk. 2015 to 2017. This research is a quantitative research, processed data, namely financial report data of PT Mustika Ratu Tbk. taken through data on the Indonesia Stock Exchange. Financial data taken is annual reports from 2015 to 2017. Analysis of this data uses liquidity ratios, solvency ratios, profitability ratios.